Peningkatan Literasi Keuangan dan Akses Permodalan Para Perempuan Pelaku Usaha Desa Klinting Kabupaten Banyumas - Poppy Dian Indira Kusuma; Dian Karunia Shalihah; Novi Tri Setyaningrum; Namira Putri Miranti; Nasilem Pangestika; Haryo Wahyu Hatmoko; Agus Khairudin Ahmadi (Pusat Riset dan Inovasi Nasional, 2025)
The community service program (PKM) carried out for women entrepreneurs in Klinting Village, Somagede District, Banyumas Regency. The program mainly aims to improve community understanding of business financial management and increase access to capital in formal financial institutions. The objectives of the PKM are achieved through socialization on business financial management and strategies for obtaining efficient capital in formal financial institutions as well as simple bookkeeping training. Through these PKM activities, the awareness of women entrepreneurs in Klinting Village about the importance of effective business financial management and financial records is expectedly increased. Women entrepreneurs were given insight into external capital sources from formal institutions, namely banks, and were introduced to effective strategies for obtaining capital from banks. In addition, entrepreneurs in Klinting Village also gain insight into the risks of informal and illegal loans, as well as how to utilize financial technology, such as digital wallets, to support their business operations. This program is expected to be able to reduce the dependence of women entrepreneurs on informal loans, encourage business sustainability, and build economic independence for the Klinting Village community. In the long term, this program has the potential to strengthen family economic stability while creating inclusive and sustainable business growth